Akuntabilitas Perencanaan dan Tata Kelola Anggaran (Studi Kasus Pada Pembangunan Mesjid Agung Al Falah Sigli - Muhammad Hanif; Ridwan Nurdin; Hendra Syahputra (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2024)
This thesis examines the accountability of budgeting and budget management in the construction of the Al-Falah Grand Mosque in Sigli. The objective of this thesis is to understand the budgeting and allocation system for the mosque's construction and to assess the committee's supervision and evaluation of the construction process. This research employs a qualitative approach with a field study methodology. The primary data sources are obtained through interviews, observations, and documentation, supplemented by secondary data to strengthen and support the primary data. The results of this study indicate that the budgeting and allocation system for the construction of the Al-Falah Mosque in Sigli is funded by the Special Autonomy Fund for Aceh, proposed by the Pidie Regency Government to the Aceh Government and the Aceh Provincial House of Representatives. The allocation of funds for the mosque's construction varies each year, with 14.21% from the Special Autonomy Fund for Aceh (DOKA) in 2015, 19.64% in 2016, and so on until 8.22% in 2022. Regarding supervision and evaluation, the Pidie Regency Government issued a Regent's Regulation to monitor and evaluate all forms of processes and stages of the mosque's construction.